2020
DOI: 10.1111/bjh.16756
|View full text |Cite
|
Sign up to set email alerts
|

Checkpoint blockade treatment sensitises relapsed/refractory non‐Hodgkin lymphoma to subsequent therapy

Abstract: Patients with relapsed/refractory (R/R) non-Hodgkin lymphoma (NHL) have limited options for salvage, and checkpoint blockade therapy (CBT) has little efficacy. Usage in solid malignancies suggests that CBT sensitises tumours to subsequent chemotherapy. We performed the first analysis of CBT on subsequent NHL treatment. Seventeen North American centres retrospectively queried records. The primary aim was to evaluate the overall response rate (ORR) to post-CBT treatment. Secondary aims included progression-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 27 publications
(32 reference statements)
0
22
0
Order By: Relevance
“…Another study showed that patients with NSCLC were more than three times more likely to achieve a partial response (PR) with salvage chemotherapy if they had prior exposure to CBT [8]. We have shown this same effect in a retrospective study of patients with non‐Hodgkin lymphoma (NHL), a disease where CBT does not appear to have much single‐agent activity [9, 10]. Given the significance of these findings, we investigated the outcome of CBT on subsequent treatment for patients with relapsed and refractory (R/R) HL in a large, multicenter, retrospective analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that patients with NSCLC were more than three times more likely to achieve a partial response (PR) with salvage chemotherapy if they had prior exposure to CBT [8]. We have shown this same effect in a retrospective study of patients with non‐Hodgkin lymphoma (NHL), a disease where CBT does not appear to have much single‐agent activity [9, 10]. Given the significance of these findings, we investigated the outcome of CBT on subsequent treatment for patients with relapsed and refractory (R/R) HL in a large, multicenter, retrospective analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Carreau and colleagues showed that the overall response to subsequent therapy after checkpoint inhibition was 62% in 81 patients with relapsed refractory Hodgkin lymphoma 94 and 51% in 59 patients with relapsed refractory non-Hodgkin lymphoma. 95 With further studies, we are hopeful that biomarkers including PD-L1 expression, TMB, and MSI status will be used to best-select patients with hematologic malignancies for treatment with checkpoint blockade who are most likely to benefit.…”
Section: Resultsmentioning
confidence: 99%
“…It is usually assumed that increasing lines of therapy will result in decreasing response rates and DOR. Given that the trend was reversed in this study, with longer DOR to therapy after CBT, the authors argue that CBT may sensitise patients to subsequent treatments 5 . These provocative data are certainly hypothesis‐generating and provide an opportunity to re‐evaluate how we approach the use CBT in NHL, as a potential ‘sensitiser’ to chemotherapy, rather than as a single agent in refractory disease.…”
mentioning
confidence: 79%
“…In this issue of the British Journal of Haematology , Carreau et al 5 . describe the outcomes of treatment beyond failure of CBT for NHL.…”
mentioning
confidence: 99%
See 1 more Smart Citation